Effect of an industrial chemical waste on the uptake of cations by green oat - Radulescu Hortensia; Taubert Lidia; Kiss Sándor A.; Princz Ecaterina; Stefanovits-Bányai Éva (Journal of the Serbian Chemical Society, 2007)
Calcium carbonate, obtained as a waste in the industrial manufacture of magnesium carbonate and magnesium oxide from dolomites, can be applied in agriculture. The appreciable amounts of calcium and magnesium in this waste, together with impurities such as iron, zinc, manganese, chromium and copper compounds can be useful in soil amendment and plant nutrition. This paper presents preliminary results of the testing of several waste doses on soil, pursuing their effect on the uptake of cations by green oat (Avena sativa L.). The obtained results show an increase in the amount of calcium, magnesium, zinc and copper found in green oat plants, as well as a decrease of the content of iron and manganese with increasing waste dose. These results may be explained by lower absorptions of iron and manganese because of the antagonistic effect created by high amounts of calcium and magnesium, as well as by the presence of copper and zinc. .